Sex-specific growth in chicks of the sexually dimorphic Black-tailed Godwit - Loonstra, A.H.J.; Verhoeven, M.A.; Piersma, T. (Ibis, 2018)
Sexual size dimorphism (SSD) is common in birds and has been linked to various selectiveforces. Nevertheless, the question of how and when the sexes start to differentiatefrom each other is poorly studied. This is a critical knowledge gap, as sex differences ingrowth may cause different responses to similar ecological conditions. In this study, wedescribe the sex-specific growth – based on body mass and five morphometric measurements– of 56 captive Black-tailed Godwit Limosa limosa limosa chicks raised under ad libitumfood conditions, and conclude that all six growth curves are sex-specific. Femalesare the larger sex in terms of body mass and skeletal body size. To test whether sex-specificgrowth leads to sex-specific susceptibility to environmental conditions, we comparedthe age-specific sizes of male and female chicks in the wild with those of Black-tailedGodwits reared in captivity. We then tested for a relationship between residual growthand relative hatching date, age, sex and habitat type in which the wild chicks were born.Early-hatched chicks were relatively bigger and in better condition than late-hatchedchicks, but body condition and size were not affected by natal habitat type. Femalechicks deviated more negatively from the sex-specific growth curves than male chicks forbody mass and total-head length. This suggests that the growth of the larger females ismore susceptible to limiting environmental conditions. On average, the deviations ofwild chicks from the predicted growth curves were negative for all measurements, whichsuggests that conditions are limiting in the current agricultural landscape. We argue thatin estimating growth curves for sexually dimorphic species, it is critical first to makeaccurate sex and age determinations.